2016
DOI: 10.2298/abs150902030k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propolis extract on hematotoxicity and histological changes induced by Salmonella enterica serovar Typhimurium in BALB/c mice

Abstract: Typhoid fever, a life-threatening disease, causes several pathological changes due to the involvement of one or more organs. In the present study, the effect of typhoid on hematological indices and spleen histology in infected mice were investigated. The ameliorative efficacy of the ethanolic extract of propolis was tested and compared with treatment with the typhoid drug,cefixime. BALB/c mice were divided into six groups: group1 was the normal control, group 2 was infected with Salmonella enteric serovar Typh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) were also calculated [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC) were also calculated [12]. …”
Section: Methodsmentioning
confidence: 99%
“…A review study have reported the antibacterial activity of propolis and its extracts against gram-positive and gram-negative bacterial strains and found that propolis has antibacterial activity against a wide range of gram-positive bacteria, but this activity is more limited in the gram-negative bacilli (54). An animal study showed that propolis could reduce the rate of infection caused by Salmonella bacteria, as well as keep WBC and neutrophil in normal levels (55). In one animal study that conducted by El-Aidy et al, propolis was able to maintain leukocyte and neutrophil at normal levels compared to other groups (56).…”
Section: Discussionmentioning
confidence: 99%
“…A review in this regard reported the antibacterial activity of propolis and its extracts against bacterial strains, indicating that propolis has antibacterial activity against a wide range of gram-positive bacteria, while the activity is rather limited in the case of gram-negative bacilli [55]. On the other hand, an animal study showed that propolis could reduce the rate of infection caused by Salmonella enterica serovar typhimurium, while maintaining normal WBC and neutrophils [56]. An animal study conducted by El-Aidy et al [57] in this regard also indicated that propolis maintained the normal levels of leukocytes and neutrophils Complement Med Res 2022;29:275-285 DOI: 10.1159/000523766 compared to the untreated group.…”
Section: Discussionmentioning
confidence: 99%